Insurgent citizenship disjunctions of democracy and modernity in Brazil - Holston, James (Princeton University Press, 2008)
This book examines the insurgence of democratic citizenship in the urban peripheries of Sao Paulo, Brazil, its entanglement with entrenched systems of inequality, and its contradiction in violence.